1996
DOI: 10.1128/jb.178.10.2836-2845.1996
|View full text |Cite
|
Sign up to set email alerts
|

Energy-coupled transport across the outer membrane of Escherichia coli: ExbB binds ExbD and TonB in vitro, and leucine 132 in the periplasmic region and aspartate 25 in the transmembrane region are important for ExbD activity

Abstract: Ferric siderophores, vitamin B 12 , and group B colicins are taken up through the outer membranes of Escherichia coli cells by an energy-coupled process. Energy from the cytoplasmic membrane is transferred to the outer membrane with the aid of the Ton system, consisting of the proteins TonB, ExbB, and ExbD. In this paper we describe two point mutations which inactivate ExbD. One mutation close to the N-terminal end of ExbD is located in the cytoplasmic membrane, and the other mutation close to the C-terminal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 61 publications
7
117
0
Order By: Relevance
“…TonB has been demonstrated to interact directly with ExbB (Larsen et al, 1994;Skare et al, 1993) and ExbB has been demonstrated to interact directly with ExbD (Braun et al, 1996). In this study, T7-ExbB and T7-ExbD localized with the cytoplasmic membrane, under conditions where chromosomally encoded TonB in the same gradients localized in both cytoplasmic membrane and outer membrane fractions.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…TonB has been demonstrated to interact directly with ExbB (Larsen et al, 1994;Skare et al, 1993) and ExbB has been demonstrated to interact directly with ExbD (Braun et al, 1996). In this study, T7-ExbB and T7-ExbD localized with the cytoplasmic membrane, under conditions where chromosomally encoded TonB in the same gradients localized in both cytoplasmic membrane and outer membrane fractions.…”
Section: Discussionsupporting
confidence: 52%
“…ExbB and ExbD localize with the cytoplasmic membrane TonB and the cytoplasmic membrane proteins ExbB and ExbD have been demonstrated to interact closely (Braun et al, 1996;Skare et al, 1993). If TonB existed in specialized regions of the cytoplasmic membrane that have a density equal to that of the outer membrane, ExbB and ExbD should also be found in these specialized high-density regions of the cytoplasmic membrane.…”
Section: Tonb Localizes With Both the Cytoplasmic And Outer Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…ExbB and ExbD, which exhibit distant homology with components of the flagellar motor, 9 appear to form a complex with TonB. 10,11 Suppressor mutation analysis has suggested that ExbB interacts with TonB through the transmembrane domain 12 while an NMR study suggested that ExbD interacts weakly with the periplasmic domain. 13 The crystal structures of several TonB-dependent receptors show a common architecture.…”
Section: Introductionmentioning
confidence: 99%
“…The conserved interaction of a family of high-affinity outer membrane (OM) transporters with the TonB complex suggests that many, if not all, gram-negative bacteria have adopted similar strategies to transport Fe across the OM. TonB is anchored in the inner membrane in association with ExbBD and spans the periplasm, presumably to transduce the energy of the proton motive force (PMF) to OM receptors (4,34,38,40). Although TonB physically interacts with OM receptors (1,8,32,45,83), the way in which TonB might convey PMF energy to these receptors to drive solute uptake remains unclear (10,46).…”
mentioning
confidence: 99%